Systemic Administration of Minocycline Reduces Fos Protein Expression in Rapid Eye Movement (REM) Sleep Deprived Rat’s Spinal Cord But Not Nociceptive Response After Formalin-Induced Inflammatory Pain - Long, Idris; Mat, Noorul Hamizah; Ab Rahman, Syarina Nurrulfatin (2017)
Minocycline is a semisynthetic second-generation tetracycline, an antibiotic that capable to penetrating the blood brain barrier and believed to have anti-inflammatory and neuroprotective effects. This study want to investigates the effects of minocycline on the nociceptive response and Fos protein expression in the spinal dorsal horn of the REM sleep deprived rat after a formalin injection. REM sleep deprivation was elicited using the modified inverted flowerpot method. Minocycline (30 mg/kg) was given intraperitoneally once a day during the 72 hours of REM sleep deprivation and 30 minutes before formalin test. Fifty microliter of formalin (2.5%) was subcutaneously injected into the plantar surface of the left hind paw of the rat. The nociceptive responses were recorded for one hour. Two hours after the formalin injection, the rats were sacrificed and expression of the Fos positive cell was examined. The nociceptive responses were found not statistically significant in all phases between all groups. However, enhancement in the number of the Fos positive cell was significantly higher in the REMsd group compared to other groups but reduced after minocycline treatment. Pre-emptive administration of minocycline reduces Fos protein expression in REM sleep deprived rat’s spinal cord but not the nociceptive response after inflammatory pain.